PENERAPAN UI/UX UNTUK PENGEMBANGAN SISTEM RUMAH SAKIT - Dhea Ismanto; Mutia Mawardah; Susan Dian Purnamasari (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This research discusses the application of User Interface (UI) and User Experience (UX) principles in the development of hospital information systems to improve the quality of health services. The research method used involved qualitative and quantitative approaches with data collection through observation, interviews, and surveys. The results showed significant improvements in user experience, measured through access speed, satisfaction levels, and reduced user error rates. Operational efficiency was also shown to improve, especially in terms of scheduling, patient monitoring, and staff information exchange. This study concludes that implementing UI/UX can have a positive impact on user experience and operational efficiency in the context of hospital systems. Therefore, hospital system developers are advised to consider UI/UX principles as an integral strategy in the development of health information systems, in order to improve the overall quality of healthcare services